Juanito - Engco, Abigail (Animo Repository, 2005)
This documentary is about a street child who chooses to reform by voluntarily entering the Don Bosco Pugad Center, a center which helps street children get out of the streets and live a safe and moral life. This center does not require the children to stay there. They are free to leave anytime they want and to continue living in the streets. However most of the children decided to stay in the center because they want to change their lives and this is the focus of the documentary.